Estimation of the k-Value for Head CT Using ICRP-103 Tissue Weighting Factors - Johan Andoyo Effendi Noor; Risalatul Latifah; Firdy Yuana (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Multi-slice x-ray CT scanners are in highly use by physicians to assist them in diagnosing patients disease due to advances in their scanning speed, image processing and image quality. However, this trend results in patients being exposed to many fold higher doses compared to those for general x-ray radiography. This makes CT machines the major source of unwanted dose to the population from medical x-ray procedures. The CTDIvol and DLP parameters are quantities of concern in radiation protection measures. This study was aimed to examine the effective dose received by patients underwent head CT procedures In this paper we present our estimation of the k-value calculated from the DLP from the CT machine in the participating hospital using the ICRP 103 weighted tissue factor. Dose parameters were acquired from the machine and calculations were carried out using the ImPACT CTDosimetry software. We also compared the received doses by age and gender groups. We found that the doses are dissimilar between age groups and between male and female patients.